SYNTHESIS, CHARACTERISATION AND ANTI INFLAMMATORY POTENTIAL OF SILVER NANOPARTICLES FROM HALOPHILA DECIPIENS SEAGRASS - Aashruthaa S, Dr. Abirami Arthanari, Dr. Sivaperumal.P,, (Chelonian Research Foundation, 2023)
AIM: To synthesise silver nanoparticles using Halophila decipiens seagrass and to evaluate the anti-inflammatory potential of the obtained formulation. INTRODUCTION: Silver nanoparticles have unique properties and are being tested for biosafety and bio distribution. They have good antimicrobial potential and anti viral potential.Halophila decipiens is a pan tropical species of Caribbean seagrass. It is a potential antioxidant and is a promising source of therapeutic products. MATERIALS AND METHODS: Dried and powdered sample of Halophila decipiens seagrass was taken and an aqueous extract was prepared.A crude extract of Halophila decipiens seagrass was prepared by heating in a water bath at 60 degrees celsius.The nanoparticles were biosynthesised using the crude extract. The nanoparticle formulation was subjected to protein denaturation assay to check its anti inflammatory activity RESULTS: The effect of crude extract of Halophila decipiens was evaluated using protein denaturation assay.The denaturation was seen as a marked attenuation in a concentration dependent manner. DISCUSSION: The results imply that the crude extract, the total flavonoid contents and the aqueous fraction of Halophila decipiens exhibited protein denaturation. The isolation of secondary metabolites will be beneficial in understanding the chemical process involved in presenting anti-inflammatory activity. CONCLUSION: The findings suggest that Halophila decipiens seagrass extracts have anti-inflammatory potential. It can also be implied that the phytochemical contents of the seagrass extracts were key in prevention of protein denaturation. Keywords: Silver nanoparticles, biosynthesis, seagrass,anti inflammatory effect,halophila decipiens